Delayed Eruption of Permanent Dentition and Maxillary Contraction in Patients with Cleidocranial Dysplasia: Review and Report of a Family. (4th July 2018) - Impellizzeri, A.; Midulla, G.; Romeo, U.; La Monaca, C.; Barbato, E.; Galluccio, G.
Abstract : Introduction . Cleidocranial dysplasia (CCD) is an inherited disease caused by mutations in the RUNX2 gene on chromosome 6p21. This pathology, autosomal dominant or caused by a spontaneous genetic mutation, is present in one in one million individuals, with complete penetrance and widely variable expressivity. Aim . To identify the incidence of these clinical findings in the report of the literature by means of PubMed interface from 2002 to 2015, with the related keywords. The report of local patients presents a clinical example, related to the therapeutic approach. Results and Discussions . The PubMed research resulted in 122 articles. All the typical signs were reported in all presented cases. The maxilla was hypoplastic in 94% of the patients. Missing of permanent teeth was found in two cases: one case presented a class II jaw relationship, instead of class III malocclusion. Similar findings were present in our cohort. Conclusion . CCD is challenging for both the dental team and the patient. The treatment requires a multidisciplinary approach. Further studies are required to better understand the cause of this disease. According to this review, a multistep approach enhances the possibilities to achieve the recovery of the most possible number of teeth, as such to obtain a good occlusion and a better aesthetic.